Adaptive gate switching control for discontinuous conduction mode DC–DC converter - Sun, Zhuochao (2013)
This paper aims to develop a novel adaptive gate switching controller (AGSC) for discontinuous conduction mode (DCM) dc-dc converters, in an attempt to reduce the power losses caused by nonideal gate switching operations. The proposed AGSC employs a dead-time controller (DTC) and a zero-current detector (ZCD) to turn ON and OFF the synchronous switch, respectively. Both the DTC and the ZCD perform self-calibration according to the converter switching node voltage, allowing the AGSC achieves near-optimal gate switching control regardless of the operating frequency, process variation, power device variation, as well as source voltage and load current variation. The proposed AGSC can have useful applications in many DCM dc-dc converters, e.g., buck, boost, and buck-boost converters. For a proof of concept, in this paper, a boost converter was implemented with the proposed AGSC in a 0.18-μm 3.3-V CMOS process with an area of 1.5 mm 2 . The experimental results demonstrate precise control of the gate switching operations, and the boost converter at 1.2-V/2.5-V nominal input/output achieves a peak efficiency of 86% at 30-mA load current.